SOME FEATURES OF TIMBER QUALITY OF BETULA PENDULA ROTH. GROWING IN CARPATHIAN AGROFORESTRY (Innovation in Woodworking Industry and Engineering design, 2026)
Betula pendula Roth has a wide natural area stretching from the forest to steppe zones in the Ukraine. Understanding the term „wood quality“ was focused on the industrial importance of the end-use of the wood product. Small-sized timbers of Silver birch growing in the Carpathian Agroforestry were mostly used for the chemical industry. In order to produce the valuable birch timbers was proposed a pruning at the stand height exceeding about 8-10 m with the pruning height of 5–6 m using clippers. The basic wood density varied from 419 till 631 kg∙m-3 with the mean value of 463–509 kg∙m-3. The coefficient of variation was almost equal to accepted reference value, because of many wood specimens from this birch stand were characterized by false core. The variables of wood shrinkage were ranged from 7.9 till 9.9% and from 4.6 till 6.6% in the tangential and radial sections respectively. The accuracy values of research results were under accepted reference value of 3.0%. It was discovered that the false core mostly reduced the wood properties of Silver birch. Two groups regards basic wood density less 499 kg∙m-3 with wood defects „false core“ and more 500 kg∙m-3 without any wood discoloration were recommended for the industrial timber scaling and the weight method of timber volume measuring.